Profit opportunity, strategic innovations, and management accounting / Akira Nishimura - Akira, Nishimura (Accounting Research Institute (ARI), 2012)
This paper reexamines the concept of profit in management accounting from the viewpoints of opportunity, profit opportunity, and strategic (feed forward) innovation. The information required today for strategic management and performance evaluation has become distinct from accounting profit information required for traditional management, given the current transitory and uncertain business environment. However, management accounting cannot exist without profit. Therefore, this paper seeks to examine the source of profit and clarify the profit opportunity-based aspects of contemporary management accounting through the analysis of opportunity, profit opportunity, and strategic innovations. For this purpose, the paper first addresses the relationship between opportunity and profit opportunity. Second, in association with management accounting, it seeks to understand current innovations intended to enhance profit opportunity. Thirdly, effects of innovations and profit opportunity on target costing in Japan are discussed. Lastly, this paper develops profit opportunity-based variance analysis that is useful in feed forward planning and feedback control processes. Increased use of strategic innovation management is found to yield more useful variance analysis and strengthen the strategic feature of management accounting, which can contribute to future innovation in management and help objectively recognize and reduce opportunity costs.